Hypermethylation of the galectin-3 promoter is associated with poor prognosis of acute-on-chronic hepatitis B liver failure. Issue 6 (June 2017) - Zhao, Jing; Fan, Yu-Chen; Liu, Xin-Yuan; Zhao, Ze-Hua; Li, Feng; Wang, Kai
Abstract: Background and aims: The possible role of g alectin-3 in acute-on-chronic hepatitis B liver failure (ACHBLF) remains unknown. This study aimed to determine the methylation status of the galectin-3 promoter in patients with ACHBLF and analyze its prognostic value. Methods: The methylation status of the galectin-3 promoter in patients with ACHBLF, chronic hepatitis B (CHB) and healthy controls (HCs) was determined by methylation-specific polymerase chain reaction (MSP). The galectin-3 mRNA level in peripheral blood mononuclear cells (PBMCs) was detected using real-time polymerase chain reaction (RT-PCR). Results: The methylation frequency of the galectin-3 promoter was significantly higher while galectin-3 mRNA was lower in ACHBLF than in CHB and HCs. Galectin-3 promoter methylation was negatively correlated with the mRNA level in ACHBLF. In addition, ACHBLF patients carrying the methylated promoter showed shorter survival time, higher 3-month mortality, and higher model for end-stage liver disease (MELD) score when compared to ACHBLF patients carrying the unmethylated promoter. Moreover, promoter methylation was a better predictor of 3-week mortality than the MELD score in ACHBLF patients. Conclusion: Our results suggest that hypermethylation of the galectin-3 promoter might be an early biomarker for predicting disease severity and prognosis in patients with ACHBLF.